The Influence of Financial Stress on Dynamic Connectedness between Fossil Energy Commodities and Green Energy Markets - Dilvin Taşkın; Efe Çağlar Çağlı; Birce Tedik Kocakaya; Pinar Evrim Mandacı (Ekonomi, Politika & Finans Araştırmaları Dergisi)
This paper aims to examine the impacts of selected stress variables, such as FSI (Financial Stress Index), VIX (Volatility Index), and EPU (Economic Policy Uncertainty), on dynamic connectedness between green markets (stocks and bonds) and fossil energy commodities. First, we employ the TVP-VAR model to measure connectedness. Then, the Fourier Cumulative Granger Causality test will be used to investigate the impacts of these stress variables on this connectedness from November 1, 2012, to November 15, 2022. The results indicate moderate return connectedness between these, mainly from short-term dynamics, suggesting that diversification may be more beneficial for long-term investments. In addition, the results indicate high connectedness during the COVID-19 pandemic. The results show high connectedness among fossil energy commodities but low connectedness among green stock and green bond markets, except for water company stocks. We observe a more significant impact of water stocks on markets, followed by oil. Our causality test results indicate that the FSI and VIX impact the connectedness between these two markets, but the connectedness influences all variables. Our results provide important implications for investors and policymakers.